1998
DOI: 10.1016/s0362-546x(97)00508-7
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Ginzburg-Landau equations of superconductivity

Abstract: Abstract. This article is concerned with the dynamical properties of solutions of the time-dependent Ginzburg-Landau (TDGL) equations of superconductivity. It is shown that the TDGL equations define a dynamical process when the applied magnetic field varies with time, and a dynamical system when the applied magnetic field is stationary. The dynamical system describes the large-time asymptotic behavior: Every solution of the TDGL equations is attracted to a set of stationary solutions, which are .divergence fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 13 publications
0
26
0
Order By: Relevance
“…This choice is realized by identifying the gauge χ with a solution of the linear parabolic equation 10) subject to the condition n · ∇χ = −n · A on the boundary. In [9], it was shown that the TDGL equations, subject to the constraint (2.9), define a dynamical system under suitable regularity conditions on H. (In the more general case, where H varies not only in space but also in time, the TDGL equations define a dynamical process.) This dynamical system has a global attractor, which consists of the stationary points of the dynamical system and the heteroclinic orbits connecting such stationary points.…”
Section: The Ginzburg-landau Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…This choice is realized by identifying the gauge χ with a solution of the linear parabolic equation 10) subject to the condition n · ∇χ = −n · A on the boundary. In [9], it was shown that the TDGL equations, subject to the constraint (2.9), define a dynamical system under suitable regularity conditions on H. (In the more general case, where H varies not only in space but also in time, the TDGL equations define a dynamical process.) This dynamical system has a global attractor, which consists of the stationary points of the dynamical system and the heteroclinic orbits connecting such stationary points.…”
Section: The Ginzburg-landau Equationsmentioning
confidence: 99%
“…see [9]. The space W 1+α,2 (Ω) is continuously imbedded in W 1,2 (Ω) ∩ L ∞ (Ω), so ψ and A are bounded and differentiable with square-integrable (generalized) derivatives.…”
Section: Asymptotic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In di!erent gauge choices, that is, for di!erent choices of the gauge function , the existence, uniqueness and regularity of solutions for TDGL equations have been studied by many authors, such as Chen et al [2], Du [3], Tang [15], Liang and Tang [12], Tang and Wang [16], TakaH c\ [14], Fleckinger-PelleH et al [6], Wang and Wang [19], Wang and Zhan [20].…”
Section: Introductionmentioning
confidence: 99%
“…In [6], the generalized Lorentz gauge, for which, "! div A with *0, was used by Fleckinger-PelleH et al Their results can be summarized as follows.…”
Section: Introductionmentioning
confidence: 99%